Analisis Sidik Jari Variasi Metode Ekstraksi Kulit Batang Tanaman Tammate (Lannea coromandelica) Menggunakan Analisis Densitometri dan Kemometrik - Syahrir, Muhammad; AR, Muh. Azwar; Khairuddin, Khairuddin; Pabunga, Chachalia; Yasir, Budiman (Herbal Medicine Journal, 2025)
Lannea coromandelica plant, commonly called tammate, is one plant that can be used as traditional medicine to treat various diseases. This plant contains metabolites that are active as antioxidants, antimicrobials, and antibacterials. This study aims to determine the fingerprint profile of L. coromandelica bark extract metabolite compounds with variations in densitometric and chemometric extraction methods. The extraction techniques used are maceration, reflux, and sonication, and the types of solvents used are aquades, 70% ethanol, ethyl acetate, and n-hexane. Each extract was analyzed by Thin Layer Chromatography (KLT)-Densitometry, and then the results were analyzed by chemometric analysis using Principle Component Analysis (PCA) and Cluster Analysis (CA). Densitometric results of almost all samples contain the same three metabolites, namely autogenerated1 (Rf 0.72, 0.76, and 0.77), autogenerated3 (Rf 0.90, 0.93, 0.94, and 0.95) and autogenerated5 (Rf 0.10, 0.11, 0.12, 0.13 and 0.15). From this study, it can be concluded that there is a similarity of L. coromandelica bark extract with a similarity value of 29,68% to 99,99%.